HEMOPHILIC INFECTION AMONG CHILDREN - A.G. Gaivoronskaya (Union of pediatricians of Russia, 2008)
In this article, the author continues dealing with issues of haemophilus influenzae in children. Modern information on the existing vaccines and efficiency of vaccination against this infection, is given. Vaccination of children with different health status deviations, which is significant in modern immunological prophylaxis, is covered in detail.Key words: hemophilic infection, vaccination, children.